2017
DOI: 10.1002/ijc.31104
|View full text |Cite
|
Sign up to set email alerts
|

The human PKP2/plakophilin‐2 gene is induced by Wnt/β‐catenin in normal and colon cancer‐associated fibroblasts

Abstract: Colorectal cancer results from the malignant transformation of colonic epithelial cells. Stromal fibroblasts are the main component of the tumour microenvironment, and play an important role in the progression of this and other neoplasias. Wnt/β‐catenin signalling is essential for colon homeostasis, but aberrant, constitutive activation of this pathway is a hallmark of colorectal cancer. Here we present the first transcriptomic study on the effect of a Wnt factor on human colonic myofibroblasts. Wnt3A regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 55 publications
2
26
0
Order By: Relevance
“…In this study, we rstly showed that WNT4 secreted by CRC cells could activate surrounding broblasts through the WNT4/βcatenin pathway. Furthermore, recent evidence suggests a signi cant role for EMT in brosis, including its involvement in tumor stroma activation [24,43]. In the current study, we showed that WNT4 prompted the nuclear translocation of β-catenin and increased the expression of α-SMA and bronectin in NFs, which subsequently enhanced reinforced cell contraction and microsphere formation.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In this study, we rstly showed that WNT4 secreted by CRC cells could activate surrounding broblasts through the WNT4/βcatenin pathway. Furthermore, recent evidence suggests a signi cant role for EMT in brosis, including its involvement in tumor stroma activation [24,43]. In the current study, we showed that WNT4 prompted the nuclear translocation of β-catenin and increased the expression of α-SMA and bronectin in NFs, which subsequently enhanced reinforced cell contraction and microsphere formation.…”
Section: Discussionsupporting
confidence: 62%
“…The WNT/β-catenin pathway is known to play an important role in CRC-associated broblasts [24,25]. To interrogate the WNT4 signaling pathways operating in CAF activation, we rst assessed activation of the β-catenin-dependent pathway using immuno uorescence assay.…”
Section: Wnt4 Promotes Broblast Recruitment and Activationvia β-Catenmentioning
confidence: 99%
“…In this paper, we showed that WNT4 could activated surrounding broblasts through WNT4/β-catenin pathway. Furthermore, recent evidence suggests a signi cant role for EMT in brosis, including its involvement in tumor stroma activation [24,36]. In our current study, WNT4 prompted the nuclear translocation of β-catenin and increased the expression of α-SMA and bronectin in NFs, which subsequently enhanced reinforced cell contraction and microsphere formation.…”
Section: Discussionsupporting
confidence: 57%
“…The WNT/β-catenin pathway is known to play an important role in CRC-associated broblast [24,25]. To interrogate the WNT4 signaling pathways operating in CAF activation, we rst assessed the activation of the β-catenin-dependent pathway using immuno uorescence.…”
Section: Wnt4 Promotes Broblast Recruitment and Activationvia β-Catenmentioning
confidence: 99%
“…We only explored the regulatory network, functional mechanism and immune infiltration of PKP2/3 in OC subsequently. In terms of potential mechanism, PKP2 could regulate the activity of Wnt/β-catenin in colon cancer-associated fibroblasts [54], and PKP2 promoted the proliferation and migration of lung cancer by activating EGFR signaling pathway [38]. In addition, PKP3 regulated autophagy and invasion of ovarian cancer through MAPK/JNK/ERK1/2/mTOR signaling pathway [13,14].…”
Section: Casesmentioning
confidence: 99%